Core plasma confinement during detachment transition with RMP application in LHD. (December 2018) - Kobayashi, M.; Masuzaki, S.; Tanaka, K.; Tokuzawa, T.; Yokoyama, M.; Narushima, Y.; Yamada, I.; Ido, T.; Seki, R.; ,
Highlights: This paper present recent analysis on the relation between core plasma transport and divertor detachment condition when the resonant magnetic perturbation (RMP) field is applied to the edge of LHD. It is found that the plasma stored energy discontinuously increases at the detachment transition, which is accompanied by pressure peaking at the central region of plasma. The application of RMP significantly changes the edge plasma profiles including the impurity radiation, which are compared to the magnetic field structure modified by the RMP. Abstract: The core plasma confinement during detachment phase is investigated in the discharges with application of resonant magnetic perturbation (RMP) field in LHD. The RMP application creates a remnant magnetic island in the edge stochastic layer, which largely changes the plasma parameter profiles including impurity radiation. The electron temperature and pressure profiles are flattened at the island, while the electron density is slightly peaked at the edge of the island. The estimated impurity radiation profile is enhanced and fixed around the magnetic island during the detached phase, where the discharge is stably sustained with controlled level of radiation. Without RMP, the radiation penetrates the confinement region, leading to radiation collapse. It is found that in the case of the RMP application the plasma stored energy increases discontinuously at the detachment transition. In spite of the reduced effective plasma volume caused by the edge magnetic island and by the enhanced radiation there, the central plasma pressure finally exceeds the case without RMP. This is caused by the pressure profile peaking at the central region in the case with RMP. These results indicate clear change of core plasma confinement during the detached phase with RMP.